Fiscal Policy in Islam (Pre-Risalah, During the Prophet's time and Rashidun Caliphs) - Royani; Yadi Janwari; Sofyan Al-Hakim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Fiscal policy is considered an integral part of the economic system governed by Islamic principles. Before the advent of Islam, the pre-Islamic Arab society had an economy based on trade, agriculture and property ownership, albeit without formal fiscal regulations. After Islam was introduced, the fiscal system began to be regulated in more detail. Zakat became an important component in fundraising to support needy Muslims and develop social infrastructure. Additionally, jizyah was also implemented, which is a tax levied on non-Muslims living under the protection of an Islamic state. During the Prophet's time, the Islamic economic approach aimed to achieve social and economic justice through fair distribution of wealth. During the reign of the Rashidun Caliphs, Islamic fiscal policy remained rooted in the principles of justice and solidarity. For example, Umar bin Khattab formulated various economic policies to support people's welfare, including land distribution to farmers, infrastructure development, and price control. Taxes and state revenues were directed to support social, religious and public interest programs. This descriptive-analytical research falls into the category of qualitative research, with a literature review approach focusing on primary materials, especially those related to Islamic economic thought.